FIGO Good Practice Recommendations on Modifiable Causes of Iatrogenic Preterm Birth. Issue 1 (22nd March 2023) - Valencia, C.M.; Mol, B.W.; Jacobsson, B.; ,
Abstract : ( Int J Gynaecol Obstet . 2021t;155:8–12) Iatrogenic preterm delivery, also known as provider-initiated preterm birth, is a planned delivery before 37 weeks of gestation. As the science of obstetrical and neonatal care practice progresses, globally iatrogenic preterm delivery has increased. Now, iatrogenic preterm delivery constitutes nearly 50% of preterm births and is increasing worldwide. Provider-initiated birth may be induction of labor or cesarean delivery without rupture of membranes or spontaneous labor. Reasons for iatrogenic preterm delivery include obstetric complications of both maternal and fetal nature. Maternal conditions include such comorbidities as hypertensive disorders of pregnancy, antepartum hemorrhage, and abnormal placentation conditions. Maternal medical conditions such as heart disease, cancer, nephropathy, and sepsis are increasing in frequency. Fetal causes such as fetal growth restriction, fetal distress, and structural malformations; and nonmedical causes may prompt iatrogenic preterm delivery. Maternal factors and provider behavior may play a role in the increasing rate of iatrogenic preterm delivery, which has led researchers to consider strategies that could decrease preterm birth rates.